Low grade astrocytomas in the West of Scotland 1987–96: treatment, outcome, and cognitive functioning. Issue 1 (1st January 2001) - Yule, S M; Hide, T A H; Cranney, M; Simpson, E; Barrett, A
Abstract : BACKGROUND: Low grade astrocytomas are among the most common central nervous system tumours in children. AIMS: To identify risk factors for the development of persistent intellectual handicap. METHODS: The notes of 30 children with histologically proven low grade astrocytoma who presented during the period 1987–96 were reviewed. Thirteen of these children who were diagnosed with intracranial tumours between 1992 and 1996 underwent cognitive assessment one year after the completion of treatment. RESULTS: Low grade astrocytomas were found in the cerebellum (59%), thalamus (17%), cerebral hemispheres (10%), and the cervical spinal cord (9%). Where possible all patients were treated with gross total resection of the tumour. Symptomatic children with tumours judged to be inoperable underwent biopsy followed by radiotherapy (13%). Three patients developed progressive disease following surgery and underwent repeat surgery and radiotherapy. Survival at a median follow up of 75 months (range 30–131) is 97%. At one year after the completion of treatment persisting cognitive impairment was common. The strongest predictor of IQ scores was the duration of symptoms of increased intracranial pressure preoperatively. CONCLUSIONS: Although the overall survival rate of children with low grade astrocytoma is excellent, significant long term disability occurs. Early diagnosis is essential to reduce postoperative cognitive morbidity.